Chaotic micromixing in open wells using audio-frequency acoustic microstreaming - Karolina Petkovic-Duran; Richard Manasseh; Yonggang Zhu; Andrew Ooi (BioTechniques)
Mixing fluids for biochemical assays is problematic when volumes are very small (on the order of the 10 µL typical of single drops), which has inspired the development of many micromixing devices. In this paper, we show that micromixing is possible in the simple open wells of standard laboratory consumables using appropriate acoustic frequencies that can be applied using cheap, conventional audio components. Earlier work has shown that the phenomenon of acoustic microstreaming can mix fluids, provided that bubbles are introduced into a specially designed microchamber or that high-frequency surface acoustic wave devices are constructed. We demonstrate a key simplification: acoustic micromixing at audio frequencies by ensuring the system has a liquid-air interface with a small radius of curvature. The meniscus of a drop in a small well provided an appropriately small radius, and so an introduced bubble was not necessary. Microstreaming showed improvement over diffusion-based mixing by 1–2 orders of magnitude. Furthermore, significant improvements are attainable through the utilization of chaotic mixing principles, whereby alternating fluid flow patterns are created by applying, in sequence, two different acoustic frequencies to a drop of liquid in an open well.